Answer:
y=3x.........1
y=x^2-10.......2
substituting value of eq 1 to 2
3x=x^2-10
x^2-10-3x=0
x^2-3x-10=0
x^2-5x+2x-10=0
X(x-5)+2(x-5)=0
(x-5)(X+2)=0
then
X=5 or X=-2
again
y=??
when X=5
y=3×5=15
when X=-2
y=-6
Answer:
Step-by-step explanation:
8p+3f=10.39
5p+4f=10.51
subtract
3p-f=-0.12
f=3p+0.12
8p+3(3p+0.12)=10.39
17p=10.39-0.36
17p=10.03
p=10.03/17=0.59
f=3×0.59+0.12=1.77+0.12=1.89 $
or 40 p+15f-40p-32f=51.95-84.08
-17f=-32.13
f=1.89 $
Answer:
It's a ray because it has a point and one line that goes on in a direction.
Step-by-step explanation:
Answer:
D
Step-by-step explanation:
The initial value is the beginning output value, or the y-value when x = 0. Therefore, since y is at 7 when x is at 0, the answer is 7.
Answer:
y = 37/4
Step-by-step explanation: